Description of nymph of Brasilocaenis atawallpa Lima, Molineri, Vieira, Pinheiro & Salles, 2019 (Ephemeroptera: Caenidae) and notes on its taxonomic status - Nascimento, Stênio R. S.; Cruz, Paulo V.; Silva, Myllena S. L.; Firmino, Viviane C.; Brasil, Leandro S.; Juen, Leandro; Lima, Lucas R. C. (Zootaxa, 2021)
Brasilocaenis atawallpa was recently described based on male imago from Colombian Amazon. The original description does not contain a designation of type specimens or locality, and it just states that the type series was studied in order to perform the cladistic analysis. In this context, we herein designate the lectotype and paralectotypes of B. atawallpa and describe its nymphal stage. The nymphs were associated to B. atawallpa by the male genitalia extracted from mature nymphs. The nymphal stage of B. atawallpa can be differentiated from others known nymphs of the genus by absence of pointed microspines on opercular gill, fore coxa without projection, middle coxa with well-developed and semicircular projection, hind coxa with finger-like projection, fore and middle tarsal claws without denticles and hind margin of the ninth sternite almost straight.